The “National Integrity Strategy (NIS): Shuddhachar Koushol” and the “Annual Performance Agreement (APA)” for Sustainable Excellence in Quality Nuclear Medicine Service (Bangladesh Journal of Nuclear Medicine, 2023)
Abstract not availableBangladesh J. Nuclear Med. 26(1): 11-12, 2023